MENGOPTIMALKAN BEASISWA PENDIDIKAN BERKELANJUTAN DI SEKOLAH TINGGI PESANTREN: MENGUBAH PARADIGMA KESEJAHTERAAN DOSEN - Maulana, Zulvan; Rofiq, Ainur (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
Objective study This is formulate and test framework management source Power integrated human resources with optimization scholarship education advanced use transform paradigm welfare lecturer multidimensionally at UIMSYA Blokagung Banyuwangi . Research This use approach qualitative with design studies case single and purposive sampling techniques for 8-11 informants key , consisting of from lecturer recipient scholarship and team HR manager . Data collected through semi- structured interviews , observation participatory , and documentation , then analyzed in a way thematic . Research results show that success of the scholarship program No only depends on the aspect funding , but also on the existence mentoring spiritual academic support mental and spiritual resilience of lecturers . In addition that , collaborative model human resource management that involves proven leaders , managers and spiritual companions increase effectiveness program implementation . Findings important other is transformation paradigm welfare lecturer of a nature materialistic going to welfare holistic which includes aspect psychological , social , spiritual, and actualization self